2009
DOI: 10.1021/jp903594a
|View full text |Cite
|
Sign up to set email alerts
|

Gas-Phase Acidities of Cysteine-Polyalanine Peptides I: A3,4CSH and HSCA3,4

Abstract: The gas-phase acidities of four cysteine-polyalanine peptides, A(3,4)CSH and HSCA(3,4), were determined using the extended Cooks kinetic method with full entropy analysis. A triple-quadrupole mass spectrometer with an electrospray interface was employed for the experimental study. The ion activation was achieved via collision-induced dissociation (CID) experiments. The deprotonation enthalpies (Delta(acid)H) of the peptides were determined to be 332.2 +/- 2.0 kcal/mol (A(3)CSH), 325.9 +/- 2.0 kcal/mol (A(4)CSH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
24
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 77 publications
5
24
0
Order By: Relevance
“…This similar behavior has been observed in the cysteine-polyalanine peptides [57]. The N-cysteine peptides, CA 3 H and CA 4 H, are more acidic than the Ccysteine ones, A 3 CH and A 4 CH, by 10 and 5 kcal/mol, respectively.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…This similar behavior has been observed in the cysteine-polyalanine peptides [57]. The N-cysteine peptides, CA 3 H and CA 4 H, are more acidic than the Ccysteine ones, A 3 CH and A 4 CH, by 10 and 5 kcal/mol, respectively.…”
Section: Discussionsupporting
confidence: 81%
“…In recent years, many of the gas-phase studies have focused on the determination of the proton affinities (and gas-phase basicities) of amino acids and peptides [33][34][35][36][37][38][39][40][41][42][43][44][45]. Although the gas-phase acidities of isolated amino acids have been studied extensively [46 -54], and the apparent acidities of multiply charged peptides have been reported [55], the information on the acidities of gas-phase neutral peptides is very limited [56,57].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous studies have demonstrated that conformations could significantly influence the gas-phase acidity of oligopeptides. For the series of cysteine (Cys)-containing peptides, the N-Cys peptides were significantly more acidic than the C-Cys peptides [34][35][36]. Computational studies suggested that the deprotonated N-Cys peptides with four residues and longer existed in a helical conformation, while the deprotonated C-Cys peptides preferred a globular conformation [35,36].…”
Section: Introductionmentioning
confidence: 99%
“…For the series of cysteine (Cys)-containing peptides, the N-Cys peptides were significantly more acidic than the C-Cys peptides [34][35][36]. Computational studies suggested that the deprotonated N-Cys peptides with four residues and longer existed in a helical conformation, while the deprotonated C-Cys peptides preferred a globular conformation [35,36]. The stronger acidity of the N-Cys peptides was mainly due to the favored interaction with the helix macro-dipole that stabilized the N-terminal thiolate anion.…”
Section: Introductionmentioning
confidence: 99%